Perception Students Taking Pronounciation On English Phonetic - Asty, Herfyna (Lembaga Penelitian dan Pendidikan Mandala, 2024)
Indonesia in order to be able to produce English pronunciation that is almost the same as native speakers. Therefore, this study was conducted to explore a series of problems that underlie the limitations of learners in producing accurate pronunciation based on their perceptions. This study used descriptive qualitative methods to present the results obtained from two instruments consisting of close-ended questionnaires with the approach of the sampling type used, namely participant in the samples, and semi-structured interviews with the type of sample, namely purposive sampling.